Košice castle in the optics of written sources - Župčán, Ladislav (Études sur la Région Méditerranéenne, 2020)
The torsos of the former castle are located approximately four and a half kilometers as the crow flies from the center of Košice. We call this site Hradová. The name Hradová probably originated from the designation of the castle, which is located on its territories. The presented study provides comprehensive information on the historical and constructional development of the little explored fortification complex in the former Abov county. The structural overview of the historical development of the castle complex is based on both a source and a literary basis. The paper is also aimed at popularizing the facts using a graphical attachment in the form of ideal 2D reconstructions.